2016
DOI: 10.1177/2058460116662299
|View full text |Cite
|
Sign up to set email alerts
|

Influence of model based iterative reconstruction algorithm on image quality of multiplanar reformations in reduced dose chest CT

Abstract: BackgroundModel-based iterative reconstruction (MBIR) reduces image noise and improves image quality (IQ) but its influence on post-processing tools including maximal intensity projection (MIP) and minimal intensity projection (mIP) remains unknown.PurposeTo evaluate the influence on IQ of MBIR on native, mIP, MIP axial and coronal reformats of reduced dose computed tomography (RD-CT) chest acquisition.Material and MethodsRaw data of 50 patients, who underwent a standard dose CT (SD-CT) and a follow-up RD-CT w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In a second step, observers evaluated the overall diagnostic image quality of FBP images of reference scans and the best-rated ASiR-V reconstruction of follow-up scans (based on the average score of independent assessments in step 1) using a 4-point scale (4 = exemplary, 3 = diagnostic, 2 = limited, 1 = non-diagnostic, as per the Radiologic Society of North America radiology lexicon). They also assessed the following IR-related specific pulmonary MDCT features and artefacts using a 4-point scale (4 = severe, 3 = moderate, 2 = mild, 1 = none): distorted appearance of the fine structures of secondary pulmonary lobules, blurring of vascular and/or bronchial borders, and hypoattenuating bands at tissue interfaces 31,32 .…”
Section: Methodsmentioning
confidence: 99%
“…In a second step, observers evaluated the overall diagnostic image quality of FBP images of reference scans and the best-rated ASiR-V reconstruction of follow-up scans (based on the average score of independent assessments in step 1) using a 4-point scale (4 = exemplary, 3 = diagnostic, 2 = limited, 1 = non-diagnostic, as per the Radiologic Society of North America radiology lexicon). They also assessed the following IR-related specific pulmonary MDCT features and artefacts using a 4-point scale (4 = severe, 3 = moderate, 2 = mild, 1 = none): distorted appearance of the fine structures of secondary pulmonary lobules, blurring of vascular and/or bronchial borders, and hypoattenuating bands at tissue interfaces 31,32 .…”
Section: Methodsmentioning
confidence: 99%
“…One of the greatest limitations of MBIR reported in the literature is the plastic appearance of final images, as reported by Barras et al [ 48 ]. In our series, we found that MBIR images are slightly superior in comparison with HIR through a subjective point-of-view, probably due to the use of very thin slices.…”
Section: Discussionmentioning
confidence: 99%
“…While the DRL is an achievable dose, there are sometimes circumstances which limit the success in achieving the optimal dose. There are specific protocols where dose may be increased, such as using thinner slices for optimal results in multiplanar reconstruction for lung screening [26,27]. Multidetector CT scanners used to produce multiplanar reconstruction images use more dose compared to single detector scanners [28].…”
Section: Discussionmentioning
confidence: 99%